Rare Variant Origin of Right Testicular Artery - A Case Report - Mamatha, Y; Prakash, BS; Padmalatha, K (Asian Journal of Medical Sciences, 2011)
Variations in the origin of arteries in the abdomen are very common but with the invention of new operative techniques within the abdomen cavity, the anatomy of abdomen vessels has assumed much more clinical importance. The gonadal arteries normally arise caudal to the renal arteries as antero-lateral branch. In contrast to classical description, very rarely originate from lumbar, common or internal iliac artery, or superior mesentric artery. Here we report a very rare case of variant origin of right testicular artery from right common iliac artery. Awareness of such variations becomes very significant and important during surgical or interventional procedures in abdomen-pelvic areas. Key words: Testicular artery; Abberrant artery; Variant origin; Renal artery; Gonadal vessels DOI: 10.3126/ajms.v2i1.3860 Asian Journal of Medical Sciences 2 (2011) 65-67